"Don't stare at it": the component-dependent relation between cognitive control and self-control. Issue 8 (17th November 2019) - Orzechowski, Jarosław; Gruszka, Aleksandra; Wójcik, Natalia; Nowak, Michał; Janik, Beata; Nęcka, Edward
ABSTRACT: The main purpose of the study was to investigate the mechanisms of self-control involved in dealing with distraction during the goal-directed performance when facing the "goal–distractor" conflict. Seventy-four volunteers (27 men) participated in the study. A spatial working memory span task was used as a goal-directed task, with three different types of distracting pictures presented peripherally: aversive stimuli, positive temptations, and neutral distractors. The participants' task was to focus on a spatial working memory span task while ignoring distractors. The obtained results indicate that different aspects of self-control can play specific roles in behaviour control, particularly in high engagement conditions. The results revealed that distractors, especially aversive stimuli that are irrelevant to the goal-directed task, are inhibited in the group with high scores on the inhibition and adjournment. However, such stimuli are carefully processed in groups with high scores on the initiative and persistence, and proactive control.